ANALYSIS OF POLYPS IN THE FEMALE REPRODUCTIVE TRACT AT HI-TECH MEDICAL COLLEGE, BHUBANESWAR, INDIA: A CROSS-SECTIONAL STUDY. - Karan, Rosy; Sharma, Ravi Kumar (Student’s Journal of Health Research Africa, 2024)
Background Polyps in the female reproductive tract, particularly endometrial and cervical polyps, are common benign lesions that can cause symptoms such as abnormal uterine bleeding (AUB), pelvic pain, and infertility. While generally benign, they may carry a risk of malignant transformation, especially in postmenopausal women. This study aims to evaluate the presence and characteristics of polyps in the female reproductive tract. Methods This cross-sectional observational study was conducted, with 80 women diagnosed with reproductive tract polyps. Clinical data were collected via patient interviews, medical records, and histopathological analysis. Statistical analyses included chi-square tests and logistic regression to identify factors associated with recurrence and malignancy. Results Most patients were aged 35-50, with 62.5% presenting with AUB. Polyps were most commonly located in the endometrium (50%) and cervix (42.5%). Histopathological examination revealed that 75% of polyps were benign, 15% were hyperplastic, and 10% showed precancerous or malignant changes. Surgical treatment via hysteroscopic polypectomy was performed in 70% of cases, and recurrence was noted in 10% of patients, with hyperplastic or malignant polyps showing a higher recurrence rate (p < 0.05). Conclusion Reproductive tract polyps are prevalent among premenopausal and postmenopausal women and are often associated with abnormal bleeding. Although most polyps are benign, a significant proportion may exhibit hyperplastic or malignant changes, particularly in older women. Surgical treatment is effective, but vigilant follow-up is necessary for patients with histopathological abnormalities due to the risk of recurrence. Recommendations Regular screening for polyps in women presenting with AUB, especially postmenopausal women, is recommended. Further studies should explore the role of hormonal and microbial factors in the development and recurrence of polyps.